Complete Genome Sequence of the Bovine Mastitis Pathogen Mycoplasma californicum Strain ST-6(T) (ATCC 33461(T)) - Calcutt, Michael J. (American Society for Microbiology, 2014)
Mycoplasma californicum is one of several mycoplasmal species associated with bovine mastitis. The complete genome sequence of 793,841 bp has been determined and annotated for the M. californicum ST-6 type strain, providing a resource for the identification of surface antigens and putative pathoadaptive features.